Aplicabilidad de los Precipitados Residuales provenientes del Tratamiento de Desechos expuestos al Cambio del estado Plasma en sólido en las Propiedades Mecánicas de los Morteros Hidráulicos - Alvarado-Briceño, Carlos Enrique (Instituto Tecnológico de Costa Rica, 2007)
The present thesis is about the generation of new alternatives in the use of construction materials; specifically about the feasibility to use artificial sand, rich in siliceous dioxide, for improve the mechanics properties of the hydraulic mortars. This sand has the special characteristic for be the final results of a crush lab process of a solid-remaining material, which is product of the state change plasma in solid; as a consequence of the process of garbage treatment, with the American system PEMTM (Plasma Enhanced MelterTM). The artificial sand will be combined with natural sand in different addition percentages, and finally tested the mechanic characteristics of the hydraulic mortars with those combinations. Besides, it will be doing different previous tests to the mortars, with the finally of determinate the physics characteristics and compatibility for both materials (artificial and natural sand) to be used as a whole. Finally, it will be doing a practical field test in a civil work with that combination of artificial-natural sand which reports the best results.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2007.
Keywords: Materiales alternativos; Propiedades mecánicas; Cambio de estado; Arena artificial; Residuos; Resistencia